The Social organization of urban water heritage and its contribution to the management of scarcity in the southern cities of Morocco - manouze, Ridouane (Journal of Humanities & Social Sciences, 2021)
This short topic talks about the issue of the social organization of the urban water heritage and its contribution to the management of scarcity in the southern cities of Morocco. We have identified this title so as to highlight the importance of water in recent years in the context of heated debate about the future of this vital material in Morocco because of the rapid climate changes that Morocco can live in the future for water scarcity, if it does not have a unified strategy to face All problems related to water scarcity، in the case of what the sky was not merciful.Therefore, I will try to study the forms of dealing with water issues in relation to the problems of scarcity through the creation of traditional social organizations and administrative and architectural techniques Contributed to positive adaptation with constraints the natural environment that does not help human stability.
Keywords: social organization of water; management of scarcity; water heritage; southern Morocco; climate change; water sustainability